Helping Developing Countries Address Public Debt Management Challenges : An IMF-World Bank Capacity Building Partnership. (Policy Papers; Policy Paper, 2013)
In 2009, the Boards of the IMF and World Bank jointly endorsed a capacity building program to help developing countries strengthen their public debt management frameworks. A key aspect of the program was to help developing countries implement the framework developed by staffs to formulate an effective medium-term debt management strategy (MTDS). The Boards also supported the continued use of the complementary framework-the Debt Management Performance Assessment (DeMPA)-developed in 2007, to assess the effectiveness of the broader institutional arrangements for public debt management. This paper provides an update on the implementation of the program since its endorsement in 2009.